Effect of physical activities on endometrium thickness and some associated variables with menstrual cycle - Saeed, Wassan (Journal of Physical Education, 2009)
In recent years ,the research attention has been focused on woman,s exercise responses and the effect of exercise on and the affect on exercise of the menstrual cycle.The purpose of this study was to investigate the effect of physical activity on endometrium thickness and some associated variables with menstrual cycle. Twenty one females females participated in this study divided in two groups ,first group included (n=8) athletes females(23.4 2.7 yrs ,55.227.003 kg, 1.60  0.11) ,and the second group included (n=13) non-athletes females(22.7 3.3 yrs ,57.06  10.2 kg, 1.56  0.14m) . endometrium thickness had been measured by ultrasound method, while the associated variables with menstrual cycle was obtained by questionnaire. The questionnaire included questions about headache, abdomen pain and back pain, pimples in the face region, breast distension, and menses pain. There was significant decrease in percentage for endometrium thickness in athletes females(%0.72) in comparison with the non-athletes females (%0.21) ,and also there was significant increase in the percentage for the associated variables with menstrual cycle in athletes females especially pimples in the face region(%0.28),while we was found a significant increase in the percentage for menses pain in non- athletes females (%0.82) in comparison with athletes females (%0.24).This study concluded that active females show decrease in percentage for endometrium thickness and increase in associated variables appearance with menstrual cycle (pimples in the face region) and decrease menses pain in comparison with non-athletes females. The percentage decrease in endometrium thickness, and percentage increase in pimples in the face region athletes females attribute to the decrease in the level for Estrogen hormone as a result of the effect of physical activity, also the hormone decrease lead to increase in androgen hormone activity that causes to appearance the pimples in the face region. Thus, this result suggest using the hormone therapy with estrogen under physician supervision in order to reduce the Effect of physical activities on endometrium thickness and some associated variables with menstrual cycle.